Potential Therapeutic Features of Human Amniotic Mesenchymal Stem Cells in Multiple Sclerosis: Immunomodulation, Inflammation Suppression, Angiogenesis Promotion, Oxidative Stress Inhibition, Neurogenesis Induction, MMPs Regulation, and Remyelination Stimulation - Abbasi-Kangevari, Mohsen; Ghamari, Seyyed-Hadi; Safaeinejad, Fahimeh; Bahrami, Soheyl; Niknejad, Hassan (Frontiers in Immunology, 2019)
Multiple sclerosis (MS) is an inflammatory and degenerative disorder of the central nervous system with unknown etiology. It is accompanied by demyelination of the nerves during immunological processes in the presence of oxidative stress, hypoxia, cerebral hypo-perfusion, and dysregulation in matrix metalloproteinases (MMPs). Human amniotic mesenchymal stem cells (hAMSC) as pluripotent stem cells possess some conspicuous features which could be of therapeutic value in MS therapy. hAMSCs could mimic the cascade of signals and secrete factors needed for promoting formation of stable neovasculature and angiogenesis. hAMSCs also have immunomodulatory and immunosuppressive effects on inflammatory processes and reduce the activity of inflammatory cells, migration of microglia and inhibit recruitment of certain immune cells to injury sites. hAMSCs attenuate the oxidative stress supported by the increased level of antioxidant enzymes and the decreased level of lipid peroxidation products. Furthermore, hAMSCs enhance neuroprotection and neurogenesis in brain injuries by inhibition of inflammation and promotion of neurogenesis. hAMSCs could significantly increase the expression of neurotrophic factor which prevent neurons from initiating programmed cell death and improve survival, development, and function of neurons. In addition, they induce differentiation of neural progenitor cells to neurons. hAMSCs could also inhibit MMPs dysregulation and consequently promote the survival of endothelial cells, angiogenesis and the stabilization of vascular networks. Considering the mentioned evidence, we hypothesized here that hAMSCs and their conditioned-medium could be of therapeutic value in MS therapy due to their unique properties including immunomodulation and inflammation suppression; angiogenesis promotion; oxidative stress inhibition; neurogenesis induction and neuroprotection; matrix metalloproteinases regulation; and remyelination stimulation.